Beginning ASP.NET 2.0 in C# 2005 From Novice to Professional - MacDonald, Matthew (Apress : Imprint: Apress, 2006)
Beginning ASP.NET 2.0 in C# 2005: From Novice to Professional steers you through the maze of ASP.NET web programming concepts. You will learn language and theory simultaneously, mastering the core techniques necessary to develop good coding practices and enhance your skill set. This book provides thorough coverage of ASP.NET, guiding you from beginning to advanced techniques, such as querying databases from within a web page and performance-tuning your site. You'll find tips for best practices and comprehensive discussions of key database and XML principles. The book also emphasizes the invaluable coding techniques of object orientation and code-behind, which will enable you to build real-world websites instead of just scraping by with simplified coding practices. By the time you finish this book, you will have mastered the core techniques essential to professional ASP.NET developers.